Corrosion characteristic of plain carbon steel coated with TiN and ZrN under high-flux ion bombardment - Kelesoglu, E; Mitterer, C; Ürgen, M (ELSEVIER SCIENCE SA, 2002)
Plain carbon steel samples (Ck 35) were coated non-reactively with TiN and ZrN by means of an unbalanced magnetron sputtering technique. Ion bombardment parameters ion energy E-1 and ion to neutral ratio J(1)/J. were systematically varied within the work. Parallel to the morphological improvement in the coatings, the samples exhibited an improved corrosion performance. The application of flux dense ion bombardment reduced the coating porosity, thus improved corrosion performance. The energetic ion bombardment reduced the inherent porosity, while it increased the possibility of arcing between substrate and chamber wall resulting in surface failures. As a result, low or mild energetic ion bombardment with high flux was assessed as a useful tool for improving corrosion performance of a coated system. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: TiN; ZrN; corrosion; plain carbon steel; unbalanced magnetron sputtering; COATING-SUBSTRATE SYSTEMS; DEPOSITION; TEMPERATURE; ENERGY; Materials Science; Physics